Adaptability and stability of accessions of a rice core collection - Bueno, Luíce Gomes; Vianello, Rosana Pereira; Rangel, Paulo Nakano; Utumi, Marley Marico; Centeno, Antônio Carlos; Pereira, José Almeida; Franco, Daniel Fernandez; Neto, Francisco Moura; Mendonça, João Antônio; Coelho, Alexandre Siqueira; Oliveira, Jaison Pereira; Brondani, Claudio (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to determine the productive potential and the genotype by environment interaction of 550 accessions of the Embrapa’s Rice Core Collection. The performance, and yield adaptability and stability of each genotype was evaluated using the additive main effects and multiplicative interactions (AMMI) approach, in nine field experiments, carried out in six Brazilian states, under dry and irrigated conditions, during three years. The linear mixed model analysis was performed, and the estimates of the variance components were obtained by the residual maximum likelihood (REML), using the best linear unbiased prediction (BLUP) procedure for the prediction of the genotypic values of random effects (EBLUP) associated with each accession. The group of accessions with better performance was the one of lines and cultivars from Brazil (LCB), as expected. However, traditional varieties (VT) were identified among the best yielding genotypes, which shows the potential of this germplasm group to contribute as a new source of genetic variability to breeding programs. Superior accessions were identified for their stability, adaptability and grain yield, among which CA880078, CA840182 and CNA00091stand out.